Experimental Study on Fatigue-Creep of P/M FGH96 Superalloy with Different Holding Time (Xibei Gongye Daxue Xuebao, 2020)
The fatigue-creep deformation characteristics and evolutions of microstructure of P/M superalloy FGH96 widely used for the turbine disc of an aero-engine were investigated experimentally. The low cycle fatigue-creep tests with different holding times were performed at 550℃. The influence of the holding time on the stress-strain curve, cyclic strain response, fatigue-creep life and damage mechanism were discussed. The results reveal that the holding time has a significant effect on the fatigue-creep deformation characteristics. As the holding time increases, the hysteretic energy of inelastic strain rises, the steady-state hysteresis curve shifts to the right and the envelope strain and the envelope strain rate increase. Fatigue-creep life decreases firstly exponentially and then stabilizes. The creep damage gradually plays a leading role. The fracture analysis indicates that the introduction of the holding time makes the section appear as a multi-crack source. The fracture mode changes from transgranular fracture to transgranular-intergranular mixed fracture. The slip bands and a small amount of dimples appear in the crack propagation zone and the dimple characteristics of the transient fracture zone are obvious.